PSYCHOLOGICAL APPROACHES TO STUDY OF OPTIMAL MANAGEMENT ACTIVITIES IN LEADERS OF ETHNIC COMMUNITY ORGANIZATIONS - N T Kolesnik (Peoples' Friendship University of Russia (RUDN University), 2015)
The article describes the main psychological approaches, and in particular, the system-synergetic approach to the study of the management activities of the leaders of ethnic community organizations. It also discusses the concept and essence of social self-organization of the ethnic group. It presents the methodological framework of the synergetic approach to the consideration of the study of complex self-organizing systems. The analysis of conditions of effectiveness of the process of self-organization of ethnic public associations is given. The basic principles of modern psychology of labor, which form the basis for the research of the optimal management activity of the leaders of ethnic community organizations, are highlighted. The presented theoretical analysis led to the conclusion that the integral research of the management activities of the heads of ethnic community organizations may be based on the psychological system-synergetic approach, from the point of which the management activities could be presented as a psychologically complex and open system.